How Transformational Leadership and Competency Supporting Employee Performance: Role of Achievement Motivation as Mediation - Anggraini, Rini; Johannes, Singmin (Asean International Journal of Business, 2024)
This research aims to analyze the influence of transformational leadership and competence on employee performance as mediated by achievement motivation in government agencies. The total population in this study was 354 employees using a purposive sampling technique with the criteria being permanent employees who had worked for more than 1 year, so the sample size was 188 employees. The data sources used are primary data obtained directly in the field such as interviews, observations and questionnaires as well as secondary data obtained from literature studies through journals, documentation, books and others. The data analysis method in this research uses Partial Least Square (PLS) with the help of SmartPLS 3.2.9 software. The results of this research show that: 1) Transformational Leadership has a positive and significant effect on employee performance at the Deputy for Corruption Eradication Commission, 2) Transformational Leadership has a positive and significant effect on Achievement Motivation, 3) Competency has a positive and significant effect on Employee Performance, 4) Competency has a positive effect and significant to Achievement Motivation, 5) Achievement Motivation has a positive and significant effect on Employee Performance, 6) Transformational Leadership has a positive and significant effect through Achievement Motivation on Employee Performance, 7) Competence has a positive and significant effect through Achievement Motivation on Employee Performance.